Determination of Air Pollution Concentrations from Motor Vehicles at Selected Stop-Points Along a Major Highway - Wuraola Abake Raji; Lukuman Jimoda; Ayobami Ajani; Adewemimo Popoola; Sunday Adebanjo (Candela Edutech Indonesia, 2026)
Intensified traffic-related air pollution along major highway corridors in developing countries poses increasing risks to environmental quality and public health. This study investigated air pollutant concentrations from motor vehicles at selected stop-points (Locations A - D) along the Benin–Ore–Sagamu highway in southwestern Nigeria. Continuous monitoring was conducted for gaseous pollutants (CO, CO₂, SO₂), particulate matter (PM2.5 and PM10), inorganic ions (SO₄²⁻ and NO₃⁻), and trace metals across four locations during wet and dry seasons. Traffic density was assessed through structured manual vehicle counts at each location, with vehicles categorized by type to assess traffic density and flow patterns. Traffic volume assessment identified Location D as the highest traffic hub, with seasonal variations influencing pollutant levels. Measured levels of CO, SO₂, PM2.5, and PM10 showed significant exceedances of WHO, NAAQS, and FMEnv guidelines, while trace metal analysis indicated extreme enrichment of Rh, Pt, Pd, and other metals, predominantly from vehicular emissions. In contrast, Fe, Zn, and Mn were predominantly derived from natural sources. Sulphate and nitrate exhibited strong dry-season correlations (r = 0.991, p < 0.01) and significant spatial variability, with ANOVA confirming the influence of location on concentrations. Wet-season deposition reduced pollutant concentrations, demonstrating the mitigating role of rainfall. The findings provide a seasonally resolved characterization of traffic-induced air pollution and emphasize the urgent need for regulatory enforcement, fuel quality improvement, and traffic management to protect public health along high-density highway corridors.